Assessment of the Role of the Social Worker in Reducing the Social Problems of the Psychiatric Patient - Nora bint Ayed Al-Mutairi (International Journal of Medical Toxicology and Legal Medicine, 2024)
The study sought to assess the social work 's effectiveness in minimizing the social, familial, and economic issues, as well as the disruption of social relationships of the mental patient. To accomplish the study goal, the social survey approach was utilised, with a questionnaire as the data collecting tool. The study sample comprised of mental patients suffering from neurotic illnesses, both male and female, who visited the clinics of the Mental Health Hospital in Buraidah, with a total of 160 patients selected using the deliberate sample technique. The study found the following conclusions about the social specialist's performance in lowering the social issues of mental patients: All axes was at an average level, with the arithmetic average falling between (1.67 and 2.34), and they are ordered as follows: The function of the social work in lowering economic issues, and arrived at an arithmetic average (2.18). The function of the social expert in minimising difficulties of social connection disorder, and arrived at an arithmetic average (217). The function of the social worker in alleviating family difficulties, and came at an arithmetic average (212), The overall field linked to the level of performance of the social expert in lowering the social challenges faced. The study proposed a number of recommendations, the most noteworthy of which are: Organizing courses for social workers on new therapeutic approaches in social service, their familiarity, and how to apply them to mentally ill patients. Intensifying specialised training courses on how to deal with the problems of the mentally ill patient for social specialists, who were unable to familiarize themselves with all the processes of professional practice in social service during the professional preparation stage in university studies. Using various approaches to develop the knowledge, skills, and capacities of social experts. Exchanging experiences both internally and externally among social workers working in the field of mental health, raising community understanding of the social worker's involvement with mental patients.